Enhancing High School Students’ Critical Thinking in Economics through Project-Based Learning Supported by E-Modules: Evidence from the Indonesia–Timor-Leste Border - Ari Data; Selvita Eka Eviana Purba; Emirensiana Adha (LP. Ma'arif Janggan Magetan, 2026)
In real life, the economy is open and continuously developing, so in its learning, critical thinking skills are needed to make it easier to understand. Students need to be taught to connect the theoretical concepts taught in the classroom with real-world situations. Project-Based Learning supported by an e-module is present to overcome this issue. However, several studies have focused on science subjects or urban contexts and have not specifically addressed border (3T) regions. In this study, we examined the effectiveness of the Project-Based Learning supported by the e-module model in improving students’ critical thinking skills in high school economics learning in the context of Indonesia’s border regions. For this purpose, we used a quasi-experimental method with a non-equivalent Control Group design involving 162 eleventh-grade students from public senior high schools in Malaka Regency, at the Indonesia–Timor Leste border. The students were divided into two groups: the experimental group, which was given the Project-Based Learning supported by e-module treatment, and the control group, which used traditional textbook-based methods. To measure students’ critical thinking skills, 20 HOTS-level questions that had been tested for validity and reliability were administered. For comparison, we analyzed the covariance (ANCOVA) test by controlling the pretest variable. The results of this study showed that the Project-Based Learning supported by the e-module proved to be more effective than the traditional method. This result was also supported by questionnaire findings showing that almost all students considered the Project-Based Learning supported by e-module learning to be interesting and enjoyable.